The radio spectral energy distribution and star-formation rate calibration in galaxies - Tabatabaei, Fatemeh; Pellegrini, Eric William (The astrophysical journal, 2017)
We study the spectral energy distribution (SED) of the radio continuum (RC) emission from the Key Insight in Nearby Galaxies Emitting in Radio (KINGFISHER) sample of nearby galaxies to understand the energetics and origin of this emission. Effelsberg multi-wavelength observations at 1.4, 4.8, 8.4, and 10.5 GHz combined with archive data allow us, for the first time, to determine the mid-RC (1-10 GHz, MRC) bolometric luminosities and further present calibration relations versus the monochromatic radio luminosities. The 1-10 GHz radio SED is fitted using a Bayesian Markov Chain Monte Carlo technique leading to measurements for the nonthermal spectral index ( ##IMG## [http://ej.iop.org/images/0004-637X/836/2/185/apjaa52bcieqn1.gif] $S_ν \sim ν ^-α _\mathrmnt$ ) and the thermal fraction ( ##IMG## [http://ej.iop.org/images/0004-637X/836/2/185/apjaa52bcieqn2.gif]